Reinjection and Induced Seismicity in Geothermal Well RN-34 in Reykjanes, Iceland - Gunnar Þorsteinsson 1994- (2021)
Reinjection is paramount to the successful and sustainable operation of any geothermal power production scheme. Reinjection has however the unfortunate drawback of occasionally inducing seismicity, a controversial phenomenon which has the potential to damage properties, power infrastructure and freshwater supplies. This thesis aims to shed light on the subject of induced seismicity by conducting a case study on well RN-34 in Reykjanes, Iceland. Earthquake locations and timings from a local seismic network are compared with injection volumetric discharge and well-head pressure. The sampling rate of the discharge and pressure, at one value per hour, are higher than previously used in this area. In total, 476 earthquakes of magnitude -0.7<M<3.9 were recorded from 2015-03-23 to 2017-11-22, with a average distance of 600 m from the injection well. Gutenberg-Richter b-value of 0.79 suggests induced seismicity. Statistical correlation is found between number of earthquake per day and reinjection temporal gradient. It is suggested that further research should be carried out using high-resolution volumetric flow and pressure data to utilize gradients for correlating well properties with seismic events. Niðurdæling jarðhitavökva er grundvöllur að sjálfbærri nýtingu jarðhitasvæða til orkuvinnslu. Sá annmarki fylgir að niðurdæling getur valdið örvaðri skjálftavirkni, sem valdið hefur titringi meðal almennings í grennd við niðurdælingarsvæði og getur valdið eignatjóni og spillt grunnvatni. Hér er rýnt nánar í orsakavalda örvaðrar skjálftavirkni í jarðhitaborholum með því að skoða holu RN-34 á Reykjanesi. Jarðskjálftavirkni er borin saman við rennsli, hitastig og þrýsting á holutoppi. Tímaupplausn gagnanna, eitt gildi á klukkustund, er betri en í fyrri rannóknum á svæðinu. Í heildina voru 476 skjálftar skráðir af stærðargráðunni -0.7<M<3.9 á tímabilinu 2015-03-23 til 2017-11-22, og var meðalfjarlægð skjálfta frá borholunni um 600 m. Gutenberg-Richter b-gildi 0.79 gefur til kynna að skjálftavirknin sé örvuð. Sýnt ...